Electronic and atomic structures of edge and screw dislocations in rock salt structured ionic crystals. Issue 24 (23rd August 2018) - Ukita, Masaya; Nakamura, Atsutomo; Yokoi, Tatsuya; Matsunaga, Katsuyuki
ABSTRACT: First-principles calculations were performed to investigate electronic and atomic structures of edge and screw dislocations in NaCl and AgCl. 1/2<110> edge and 1/2<110> screw dislocations, which are the ones due to the easiest slip system of these crystals, were treated in a first-principles manner. It was found that the edge dislocation has extended core structures over several atomic planes in both NaCl and AgCl. In contrast, the screw dislocation in AgCl showed the different shear strain around the dislocation core from that in NaCl although the one has a similar atomic structure in the two crystals. Local electronic structures around the dislocation cores in AgCl exhibit larger bonding interactions between atomic orbitals than those in NaCl, indicating that covalent interactions are more significant at the dislocation cores of AgCl. From excess dislocation energies, it was found that the dislocations in AgCl are much more stable than those in NaCl. Especially, the screw dislocation of AgCl has much smaller core energy than that of the edge dislocations. This suggests that the screw dislocations can be easily formed and multiplied in AgCl, which may be closely related to the observed ductility of AgCl.